A Systematic Review of In vitro and In vivo Activities of Anti-Toxoplasma Drugs and Compounds (2006–2016) - Montazeri, Mahbobeh; Sharif, Mehdi; Sarvi, Shahabeddin; Mehrzadi, Saeed; Ahmadpour, Ehsan; Daryani, Ahmad (Frontiers in Microbiology, 2017)
The currently available anti-Toxoplasma agents have serious limitations. This systematic review was performed to evaluate drugs and new compounds used for the treatment of toxoplasmosis. Data was systematically collected from published papers on the efficacy of drugs/ compounds used against Toxoplasma gondii (T. gondii) globally during 2006-2016. The searched databases were PubMed, Google Scholar, Science Direct, ISI Web of Science, EBSCO, and Scopus. One hundred and eighteen papers were eligible for inclusion in this systematic review, which were both in vitro and in vivo studies. Within this review, 80 clinically available drugs and a large number of new compounds with more than 39 mechanisms of action were evaluated. Interestingly, many of the drugs/ compounds evaluated against T. gondii act on the apicoplast. Therefore, the apicoplast represents as a potential drug target for new chemotherapy. Based on the current findings, 49 drugs/ compounds demonstrated in vitro half-maximal inhibitory concentration (IC50) values of below 1 μM, but most of them were not evaluated further for in vivo effectiveness. However, the derivatives of the ciprofloxacin, endochin-like quinolones and 1-[4-(4-nitrophenoxy) phenyl] propane-1-one (NPPP) were significantly active against T. gondii tachyzoites both in vitro and in vivo. Thus, these compounds are promising candidates for future studies. Also, compound 32 (T. gondii calcium-dependent protein kinase 1inhibitor), endochin-like quinolones, miltefosine, rolipram abolish, and guanabenz can be repurposed into an effective anti-parasitic with a unique ability to reduce brain tissue cysts (88.7 %, 88%, 78%, 74%, and 69%, respectively). Additionally, no promising drugs are available for congenital toxoplasmosis. In conclusion, as current chemotherapy against toxoplasmosis is still not satisfactory, development of well-tolerated and safe specific immunoprophylaxis in relaxing the need of dependence on chemotherapeutics is a highly valu¬able goal for global disease control. However, with the increasing number of high-risk individuals, and absence of a proper vaccine, continued efforts are necessary for the development of novel treatment options against T. gondii. Some of the novel compounds reviewed here may represent good starting points for the discovery of effective new drugs. In further bioinformatic and in silico studies are needed in order to identify new potential toxoplasmicidal drugs.